2015
DOI: 10.1515/tnsci-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

BDNF/Trk/KCC2 pathway in nicotine withdrawal-induced hyperalgesia

Abstract: PurposeTo investigate the effect of brain-derived neurotrophic factor (BDNF)/tropomyosin receptor kinase (Trk) on potassium chloride cotransporter 2 (KCC2) in rats following nicotine withdrawal and the roles played by BDNF/Trk/KCC2 pathway in nicotine withdrawal-induced hyperalgesia.MethodsSeventy-eight rats were randomly assigned to five groups: control group (n = 12) without any treatment, normal saline group (NS group, n = 12) and nicotine withdrawal group (NW group, n = 30) receiving a subcutaneous injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Shi Wenhui et al. (Shi W et al., 2015) found that the BDNF–TrkB–KCC2 pathway is involved in nicotine‐withdrawal‐induced anaphylactic pain. In animal models of inflammatory pain, neuropathic pain, and opioid‐induced hyperalgesia (Liu et al., 2017; Yajima et al., 2005) BDNF has been shown to downregulate KCC2 expression by activating the TrkB receptor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi Wenhui et al. (Shi W et al., 2015) found that the BDNF–TrkB–KCC2 pathway is involved in nicotine‐withdrawal‐induced anaphylactic pain. In animal models of inflammatory pain, neuropathic pain, and opioid‐induced hyperalgesia (Liu et al., 2017; Yajima et al., 2005) BDNF has been shown to downregulate KCC2 expression by activating the TrkB receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Potassium chloride co-transporter 2 (KCC2) is a major Cl − extruder in the central nervous system and plays a major role in Cl − homeostasis (Coull et al, 2005). Shi Wenhui et al (Shi W et al, 2015) found that the BDNF-TrkB-KCC2 pathway is involved in nicotine-withdrawalinduced anaphylactic pain. In animal models of inflammatory pain, neuropathic pain, and opioid-induced hyperalgesia (Liu et al, 2017;Yajima et al, 2005) BDNF has been shown to downregulate KCC2 expression by activating the TrkB receptor.…”
Section: Introductionmentioning
confidence: 99%